Modelling of residual stress relaxation : a review - Zaroog, Omar Suliman; Ali, Aidy; Sahari, Barkawi; Zahari, Rizal (Universiti Putra Malaysia Press, 2009)
Compressive residual stress, induced by mechanical surface treatment, may relax during component operation life, due to thermal or mechanical mechanism. Fatigue life prediction for the components which have residual stress will be misled and inaccurately predicted the phenomenon of residual stress relaxation is not considered. Despite putting an effort on incorporating the residual stress relaxation, the issues remain concerned with the technical challenge of measuring and quantifying the magnitude of residual stress relaxation as well as redistribution during the loading cycling itself. In this paper, the residual stress relaxation and its models were reviewed and discussed to picture the best knowledge related to this topic, i.e. whether relaxation is a cause or an effect.